2015
DOI: 10.2174/1871526515666150826114745
|View full text |Cite
|
Sign up to set email alerts
|

<i>Acinetobacter lwoffii</i> An Emerging Pathogen in Neonatal ICU

Abstract: Multi drug resistant Acinetobacter lwoffii infection is increasing particularly in premature and very low-birth weight neonates. Judicious and timely antibiotic use in NICUs are one of the important key in controlling multi-drug resistant Acinetobacter infection and improving clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…These bacteria are not considered priority pathogens on WHO's published list of antibiotic–resistant “priority pathogens” (Lawe-Davis and Bennett, 2017). Despite this, it should be emphasized that A. Iwoffii , which is ubiquitous in the environment is an emerging multidrug resistant pathogen in neonatal sepsis (Mittal et al, 2015). Furthermore, ARGs encoding for resistance against cephalosporins, macrolides, polymyxins, quinolones, and aminoglycosides, that are categorized as critically important antimicrobials for human medicine by WHO (2016), persisted throughout the wastewater treatment process.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are not considered priority pathogens on WHO's published list of antibiotic–resistant “priority pathogens” (Lawe-Davis and Bennett, 2017). Despite this, it should be emphasized that A. Iwoffii , which is ubiquitous in the environment is an emerging multidrug resistant pathogen in neonatal sepsis (Mittal et al, 2015). Furthermore, ARGs encoding for resistance against cephalosporins, macrolides, polymyxins, quinolones, and aminoglycosides, that are categorized as critically important antimicrobials for human medicine by WHO (2016), persisted throughout the wastewater treatment process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, no C. elegans in vivo-studies concerning these two bacteria have been reported in the literature, but their potential pathogeny for humans is well known. Bacteremia and infections caused by A. iwoffii and M. luteus are mostly registered as healthcare-associated infections [69][70][71][72]. In comparison with other microorganisms, the two isolates showed certain pathogenic behaviors because they caused all the typical symptoms and phenotypes of a C. elegans infection, as reported by Ewbank and Pujol [73].…”
Section: In Vivo Assaymentioning
confidence: 79%
“…Among the more frequent non- baumannii Acinetobacter species causing infections, we found A. junii, A. soli, A. ursingii, A. nosocomialis and A. lwoffii [3] , [4] , [5] . However, A. schindleri, which was first described in isolates recovered mostly from nonsterile body sites of outpatients, has not been reported in clinically significant isolates from seriously ill hospitalized patients.…”
mentioning
confidence: 79%